Accused stripped of the power to elect to have trials before a jury of their peers - Boersig, J.; Campbell, J.; Carmichael, S. (Current issues in criminal justice, 2021)
On 2 April 2020, the COVID-19 Emergency Response Act 2020 (ACT) made amendments to address the ongoing - and, at that stage, escalating - COVID-19 outbreak. Amongst its provisions, the Act amended the Supreme Court Act 1933 (ACT) to allow judge-alone trials on indictable offences, at the election of a judge. This article assesses the rationale for this amendment, finding that the concerns expressed by the Australian Capital Territory (ACT) legislature that delay in justice would have negative ramifications are merited. The evidence demonstrates that delay in trial proceedings can negatively affect witness memory, prolong victim and witness trauma, and harm defendants through indeterminate incarceration. However, the authors express reticence about the constitutional legality of waiving such a fundamental right through territory legislation. There are multiple constitutional grounds on which the legislation can be challenged, with this article exploring the possible implications of the Kable Doctrine. The authors' comparison to New South Wales (NSW) and Victoria shows that there were more appropriate measures that balanced the swift execution of justice and interests of an accused. The right to trial by a jury of peers is a bedrock of Australian law and the decision to abrogate that right represents a dangerous precedent.